1,5-hydrogen transfer - A hitherto ignored decay channel in the photodegradation of poly(2,6-dimethyl-1,4-phenylene oxide) - Schneider, Siegfried; Gedeck, Peter; Clark, Timothy; et al. (Chemical Physics Letters, 1996)
We present the results of a theoretical study and pur forward a novel mechanism for the photodegradation of the polymer poly (2,6-dimethyl-1,4-phenylene oxide) (PPE). The primary step is a 1,5-hydrogen transfer from the methyl group of one ring system to the ipso-carbon of the adjacent monomeric unit. Therefore, in contrast to other proposed mechanisms, the primary step is a result of the three-dimensional structure of PPE rather than a consequence of structural defects in the polymer chain or of impurities.